Hidup publik Yesus: perspektif multikulturalisme dan relevansinya bagi peleyanan disabilitas di Toraja jemaat Loko’ - Semar Paonganan (STIPAS Keuskupan Agung Kupang, 2025)
This study aims to examine Jesus' public life from a multicultural perspective and his contribution to ministry to people with disabilities in Rantebua, North Toraja. Multiculturalism is not only understood as a recognition of religious and cultural diversity, but also as an appreciation for the diversity of human life, including that of people with disabilities. People with disabilities are often viewed as second-class citizens due to their abnormal conditions. In the Rantebua context, people with disabilities are often overlooked in community services and within the church. Therefore, a theological study is needed to educate the community so that people with disabilities receive care and fair treatment. This study used a qualitative method with a library research approach through a review of literature on public theology and multiculturalism. The results show that Jesus' public life demonstrated an open attitude toward all people, including people with disabilities, by restoring their physical and spiritual dignity. As the Church in Rantebua, the Loko' congregation needs to emulate Jesus' compassionate attitude in providing equal service, respecting, and embracing people with disabilities. The church must be the body of Christ and a community of people with disabilities.